Influence of lightweight alloying elements on the microstructural evolution and thermodynamic complexity of powder metallurgy high-entropy alloys - 이한성 (The Graduate School, Ajou University, 2024)
High-entropy alloys (HEAs) are an innovative class of materials formed by alloying five or more elements in nearly equiatomic or similar proportions. This innovative approach surpasses traditional alloy paradigms, offering superior mechanical properties and unique features. HEAs are known for their flexible design and exceptional properties, including high strength and high-temperature stability, making them suitable for extreme environments and refractory applications. The four core effects of HEAs make differences compared to conventional alloys. To design these advanced materials, it is crucial to consider thermodynamic complexity and satisfy various thermodynamics. Despite these challenges, HEAs exhibit high specific strength, toughness, excellent high-temperature stability, fatigue resistance, and corrosion resistance, making them ideal for aerospace, nuclear fusion, and high-pressure turbine applications._x000D_ This study aims to stably incorporate lightweight elements with distinct thermodynamic characteristics into HEAs based on thermodynamic complexity, using powder metallurgy (PM). By analyzing the microstructure and mechanical properties, the study seeks to elucidate the strengthening mechanisms and explore the effects of microstructural changes induced by the addition of lightweight elements. _x000D_ The research explores the thermodynamic complexity and examines how the addition of non-metallic silicon influences phase formation, lattice structure, and mixed bonding in FeCoNiAlSi system HEAs. The findings indicate that silicon addition leads to significant lattice distortion, changes in valence electron concentration (VEC), and mixed bonding effects, influencing the microstructural evolution from FCC + BCC to BCC/B2 phases. Mechanical properties vary with microstructure, showing increased hardness and strength but reduced fracture strain with higher Si content. The study identifies optimal compositions, such as FeCoNiAlSi0.2, which balances strength and ductility._x000D_ In a parallel effort, the research investigates FeMnAlTiSiMg system ultra-lightweight HEAs to explore the effects of lightweight elements on specific strength. Results show that these alloys, fabricated via PM, achieve high specific strength (up to 480 MPa·m³/kg), comparable to conventional titanium alloys. The optimal composition, FeMnAlTiSiMg0.25, exhibits a refined BCC/B2 structure with enhanced mechanical properties due to grain refinement and maximized lattice distortion._x000D_ Overall, this dissertation demonstrates the potential of HEAs designed with thermodynamic complexity and lightweight elements for use in extreme environments. The findings contribute to advancing the understanding of HEAs to enhance the mechanical properties of HEAs developed through PM.
학위논문(박사)--에너지시스템학과,2024. 8
Keywords: High-entropy alloys; lightweight; microstructure; powder metallurgy; thermodynamic